Production of Knowledge in the Master' Program in Collective Health of the Faculty of Nursing at Universidad de Antioquia, 1996-2013 - María Angélica Arzuaga; Alba Helena Correa; Inna Elida Florez-Torres (Universidad de Antioquia, 2015)
Objective. This work sought to characterize the scientific production of the degree works in the Master' in Collective Health (MCH) of the Faculty of Nursing at Universidad de Antioquia, during the period from 1996 to 2013. Methodology. Ours was a descriptive, observational study, based on documentary research and content analysis. The work analyzed the degree works presented in the MCH since 1996 until 2013, reported in the library of the Faculty of Nursing, and the scientific articles published. These were reviewed manually using an instrument containing the variables of the characteristics of the works and articles. Results. Some 51 degree works were included, corresponding to eight cohorts from the Master' in which 65 master' students have graduated and 61 professors have participated as counselors. The most common themes have been Gender and Health (27%) and Food and Nutrition Safety (16%). The most frequent populations object of study were women (14%) and population groups and/or community (14%). The methodologies used have been 90.2% qualitative, 3.9% quantitative, and 5.9% mixed. A total of 52.9% of the degree works were published as articles in scientific journals; of these, 46.49% corresponded to A2 journals, according to the classification by COLCIENCIAS. Conclusion. The characteristics of the degree works show increased dissemination in scientific journals, as well as diversification in the populations object of study and progress in the dissemination of the knowledge generated in the MCH, thus, contributing to progress in collective health in national and international settings.